Clinical profile of an unselected population with heart failure treated with vericiguat in real life: differences with the VICTORIA trial - Esteban-Fernández, Alberto; Recio-Mayoral, Alejandro; López-Vilella, Raquel; de Lara, Gregorio; Barrantes-Castillo, Moisés; Gómez-Otero, Inés; Nuñez-Villota, Julio; Robles-Gamboa, Carolina; López-Aguilera, José; Iniesta-Manjavacas, Ángel; Fluviá, Paula; Pastor-Pérez, Francisco; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionVericiguat, an oral stimulator of soluble guanylate cyclase, reduces cardiovascular mortality and hospitalisations in patients with heart failure (HF) and reduced ejection fraction, as demonstrated in the VICTORIA trial. This study assessed the real-world use of vericiguat.Material and methodsThis cross-sectional, prospective and multicenter registry (VERISEC) included 776 patients from 43 centres in Spain between December 2022 and October 2023. Of these patients, 79.6% were male, with a mean age of 72.4 (SD:8.7) years. Patients in VERISEC were older and had more comorbidities (diabetes, advanced chronic kidney disease) compared to VICTORIA, with 20% having an estimated glomerular filtration rate below 30 ml/min. They also had higher natriuretic peptide levels [NT-proBNP: 3551 (IQR: 1,675.9, 7,054.0)] pg/ml. Most patients (79.8%) started vericiguat after HF decompensation within the previous three months, with high use of loop diuretics (with an average dose of 65 mg/day) and implanted devices (50%). Sixty percent of patients were on quadruple therapy, with a higher use of sodium-glucose co-transporter 2 inhibitors compared to the VICTORIA trial. Despite the more severe disease in the VERISEC cohort, the implementation of guideline-directed medical therapy was greater than in VICTORIA, although vericiguat was initiated at lower blood pressure levels.ConclusionsPatients in the VERISEC registry had more severe illness and higher comorbidities compared to those in the VICTORIA, despite receiving optimised treatments. Further research is needed to identify which patients may benefit the most from vericiguat treatment.